Phonon anomaly and local distortion in iron-manganese-based Elinvar alloys - Yoshihiko Umemoto; Yoichi Ikeda; Takashi Honda; Daisuke Ishikawa; John A. Schneeloch; Jörg C. Neuefeind; Shinichiro Tozawa; Rie Umetsu; Despina Louca; Alfred Q.R. Baron; Masaki Fujita (Science and Technology of Advanced Materials, 2025)
This paper examines the phonon dispersion and static local atomic distortion of iron-manganese-based Elinvar alloys using high-resolution inelastic X-ray scattering, magnetization, neutron diffraction, and neutron total scattering. In this study, nonlinear phonon dispersion was observed for a transverse acoustic mode near zone center, associated with [Formula: see text] elastic constants, over a wide temperature range along the [Formula: see text] to X (310) points of the face-centered cubic system, indicating lattice instability coupled with tetragonal distortions in the long-wavelength limit. Bulk magnetization and neutron diffraction measurements suggest that the conventional ferromagnetic magnetostriction scenario is not the origin of Elinvar characteristics. Instead, the martensitic transformation and lattice instabilities underlie these phenomena. The reduced pair distribution function reveals a significant discrepancy between local and global (averaged) structures suggesting the influence of atomic-scale lattice disorder and instability in FeMn-based Elinvar alloys.